2017
DOI: 10.2147/gictt.s139944
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on hyperthermic intraperitoneal chemotherapy in gastric cancer

Abstract: Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is an effective treatment in a variety of cancers with peritoneal carcinomatosis (PC), especially in pseudomyxoma peritonei for which it is the standard of care. The data for gastric cancer are not as conclusive. This review discusses the effect of HIPEC on gastric cancer survival, the importance of patient selection, the effect of HIPEC on gastric cancer morbidity, translational research on HIPEC, and other recent research on HIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Our analysis suggested that CRS combined with HIPEC may enhance short-term survival in patients, with 2-year and 3-year survival rates of 28.70% and 9.60%, respectively. The median survival duration for individuals in the HIPEC cohort was 20.00 ± 4.89 months, consistent with the findings of Smith et al [ 11 ]. Liu’s et al meta-analysis of 21 randomized controlled trials, encompassing 1674 participants, demonstrated a significantly greater 3-year survival rate in patients receiving HIPEC than in those who did not[ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis suggested that CRS combined with HIPEC may enhance short-term survival in patients, with 2-year and 3-year survival rates of 28.70% and 9.60%, respectively. The median survival duration for individuals in the HIPEC cohort was 20.00 ± 4.89 months, consistent with the findings of Smith et al [ 11 ]. Liu’s et al meta-analysis of 21 randomized controlled trials, encompassing 1674 participants, demonstrated a significantly greater 3-year survival rate in patients receiving HIPEC than in those who did not[ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…Due to the drawbacks of noninvasive image modalities, diagnostic laparoscopy remains a useful method to clarify peritoneal carcinomatosis with the highest accuracy [ 7 , 8 ]. Furthermore, cytoreductive surgery (CC0 or CC1) plus hyperthermic intraperitoneal chemotherapy might offer an alternative to improve the overall survival for fit patients with a peritoneal cancer index score < 12 [ 9 ]. However, a large-scale randomized trial is needed to validate this approach.…”
mentioning
confidence: 99%